High Frequency Stimulation of the Pelvic Nerve Inhibits Urinary Voiding in Anesthetized Rats - Crook, Jonathan J.; Lovick, Thelma A. (Frontiers in Physiology, 2017)
Urge Urinary Incontinence: ‘a sudden and uncontrollable desire to void which is impossible to defer’ is extremely common and considered the most bothersome of lower urinary tract conditions. Current treatments rely on pharmacological, neuromodulatory and neurotoxicological approaches to manage the disorder, by reducing the excitability of the bladder muscle. However, some patients remain refractory to treatment. An alternative approach would be to temporarily suppress activity of the micturition control circuitry at the time of need i.e. urgency. In this study we investigated, in a rat model, the utility of high frequency pelvic nerve stimulation to produce a rapid onset, reversible suppression of voiding. In urethane-anaesthetised rats periodic voiding was induced by continuous infusion of saline into the bladder whilst recording bladder pressure and electrical activity from the external urethral sphincter. High frequency (1-3kHz), sinusoidal pelvic nerve stimulation initiated at the onset of the sharp rise in bladder pressure signalling an imminent void aborted the detrusor contraction. Urine output was suppressed and tone in the external urethral sphincter increased. Stimulating the right or left nerve was equally effective). The effect was rapid in onset, reversible and reproducible and evoked only minimal ‘off target’ side effects on blood pressure, heart rate, respiration, uterine pressure or rectal pressure. Transient contraction of abdominal wall was observed in some animals. Stimulation applied during the filling phase evoked a small, transient rise in bladder pressure and increased tonic activity in the EUS, but no urine output. Suppression of micturition persisted after section of the contralateral pelvic nerve or after ligation of the nerve distal to the electrode cuff on the ipsilateral side. We conclude that high frequency pelvic nerve stimulation initiated at the onset of an imminent void provides a potential means to control urinary continence.